2018
DOI: 10.1016/j.ijmecsci.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model for subsurface microstructure prediction in micro-machining Ti-6Al-4V alloy – Experimental validation

Abstract: In this study, a new multiscale framework based on 2.5D discrete dislocation dynamics is proposed to predict the subsurface damaged layer evolution in micro-milling titanium alloy Ti-6Al-4V. This model takes into account the characteristics of component microstructure transformation and grain refinement by tracking the movement of matrix defects such as multiplication, slip, climb, cross-slip, junction and annihilation. Meanwhile, to understand the size dependence effect in micro-machining operation, a novel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In order to analyze the effects of machining parameters (spindle speed n, feed per tooth fz, axial milling depth ap, and radial milling depth ae) on machining quality, an orthogonal experiment is designed, ignoring the interaction among all the parameters. The Taguchi experiment table L16 (4 4 ) is chosen for experiment design, and the process parameters and their levels are shown in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to analyze the effects of machining parameters (spindle speed n, feed per tooth fz, axial milling depth ap, and radial milling depth ae) on machining quality, an orthogonal experiment is designed, ignoring the interaction among all the parameters. The Taguchi experiment table L16 (4 4 ) is chosen for experiment design, and the process parameters and their levels are shown in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, it is increasingly used in the processing of thin-walled microscale parts. However, both the thin-walled microscale part and micro-milling tools have weak stiffness, which brings challenges for its fabrication, especially for difficult-to-machine materials like Ti-6Al-4V alloy [4] . So, it is necessary to further investigate the machining process of thin-walled microscale parts.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of high-speed cutting, the plastic deformation of the machined surface is serious, the grains are elongated and broken, the original morphology is changed, and the surface lattice distortion and dislocation movement are also intensified. This causes the machined surface grains to become refined, internal stress is generated between the grains and microcrystals, and, finally [23], the diffraction peak width increases. The XRD spectra of 7050 aluminum alloy at different cutting depths…”
Section: Xrd Analysis Of the Machined Surface Layer At Different Cutt...mentioning
confidence: 99%
“…Ginting et al [9] reported the dependence of the surface integrity properties, including roughness, defects, microhardness, and microstructure on machining parameters in dry milling titanium alloy. Bai et al [10] studied the dislocation distribution at subsurface damage layer in micro-milling Ti-6Al-4V, and pointed out that the work hardening effect might attribute to the dislocations piling-up zone and persistent slip band observed at the machined subsurface. However, it is recognized that the fundamental research on the microstructural evolution processes in high-performance cutting requires many experimental matrices and cumbersome procedures of nano-characterization tests.…”
Section: Introductionmentioning
confidence: 99%